Pilot study: an acute bout of high intensity interval exercise increases 12.5 h GH secretion. Issue 2 (22nd January 2018) - Deemer, Sarah E.; Castleberry, Todd J.; Irvine, Chris; Newmire, Daniel E.; Oldham, Michael; King, George A.; Ben‐Ezra, Vic; Irving, Brian A.; Biggerstaff, Kyle D.
Abstract: The purpose of this study was to test the hypothesis that high‐intensity interval exercise (HIE) significantly increases growth hormone (GH) secretion to a greater extent than moderate‐intensity continuous exercise (MOD) in young women. Five young, sedentary women (mean ± SD; age: 22.6±1.3 years; BMI: 27.4±3.1 kg/m 2 ) were tested during the early follicular phase of their menstrual cycle on three occasions. For each visit, participants reported to the laboratory at 1700 h, exercised from 1730–1800 h, and remained in the laboratory until 0700 h the following morning. The exercise component consisted of either 30‐min of moderate‐intensity continuous cycling at 50% of measured peak power (MOD), four 30‐s "all‐out" sprints with 4.5 min of active recovery (HIE), or a time‐matched sedentary control using a randomized, cross‐over design. The overnight GH secretory profile of each trial was determined from 10‐min sampling of venous blood from 1730–0600 h, using deconvolution analysis. Deconvolution GH parameters were log transformed prior to statistical analyses. Calculated GH AUC (0–120 min) was significantly greater in HIE than CON ( P  = 0.04), but HIE was not different from MOD. Total GH secretory rate (ng/mL/12.5 h) was significantly greater in the HIE than the CON ( P  = 0.05), but MOD was not different from CON or HIE. Nocturnal GH secretion (ng/mL/7.5 h) was not different between the three trials. For these women, in this pilot study, a single bout of HIE was sufficient to increase 12.5 h pulsatile GH secretion. It remains to be determined if regular HIE may contribute to increased daily GH secretion. Abstract : Growth hormone (GH) is a potent lipolytic hormone that is secreted primarily at night and in a dose‐dependent response to exercise. We aimed to determine if high‐intensity interval exercise increased both total and overnight GH secretion compared to moderate‐ intensity exercise or no exercise. It was determined that an acute bout of high‐intensity interval exercise increases GH secretion compared to no exercise, but it was not different from moderate‐intensity exercise.